
5个回答
展开全部
x=16(√17-1)/(√17-1)(√17+1)=√17-1
x+1=√17
平方
x²+2x+1=17
x²+2x=16
原式=x^3(x²+2x)-17x^3-x²+18x-17
=16x^3-17x^3-x²+18x-17
=-x^3-x²+18x-17
=-x^3-2x²+x²+18x-17
=-x(x²+2x)+x²+18x-17
=-x*16+x²+18x-17
=x²+2x-17
=16-17
=-1
x+1=√17
平方
x²+2x+1=17
x²+2x=16
原式=x^3(x²+2x)-17x^3-x²+18x-17
=16x^3-17x^3-x²+18x-17
=-x^3-x²+18x-17
=-x^3-2x²+x²+18x-17
=-x(x²+2x)+x²+18x-17
=-x*16+x²+18x-17
=x²+2x-17
=16-17
=-1
展开全部
x=16/√17+1=√17-1
则(x+1)^2=17
化简得 x^2+2x = 16
原式=x^3(x2+2x)-17x^3-x2+18x-17
=16x^3-17x^3-x2+18x-17
=-x^3-x2+18x-17
=-x^3-2x2+x2+18x-17
=-x(x2+2x)+x2+18x-17
=-x*16+x2+18x-17
=x2+2x-17
=16-17
=-1
则(x+1)^2=17
化简得 x^2+2x = 16
原式=x^3(x2+2x)-17x^3-x2+18x-17
=16x^3-17x^3-x2+18x-17
=-x^3-x2+18x-17
=-x^3-2x2+x2+18x-17
=-x(x2+2x)+x2+18x-17
=-x*16+x2+18x-17
=x2+2x-17
=16-17
=-1
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
x=16/√17+1=√17-1
则(x+1)^2=17
化简得 x^2+2x = 16
x^5+2x^4-17x^3-x^2+18x-16
= x^3(x^2+2x) -17x^3-x^2+18x-17
= 16x^3 -17x^3-x^2+18x-17
= -x^3 - x^2 +18x-17
= -x(x^2+2x) +x^2 +18x-17
= -16x +x^2+18x-17
= x^2+2x -17
= 16 -17
= -1
则(x+1)^2=17
化简得 x^2+2x = 16
x^5+2x^4-17x^3-x^2+18x-16
= x^3(x^2+2x) -17x^3-x^2+18x-17
= 16x^3 -17x^3-x^2+18x-17
= -x^3 - x^2 +18x-17
= -x(x^2+2x) +x^2 +18x-17
= -16x +x^2+18x-17
= x^2+2x -17
= 16 -17
= -1
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
1.x=16(√17-1)/(√17-1)(√17+1)=√17-1
x+1=√17
平方
x²+2x+1=17
x²+2x=16
原式=x^3(x²+2x)-17x^3-x²+18x-17
=16x^3-17x^3-x²+18x-17
=-x^3-x²+18x-17
=-x^3-2x²+x²+18x-17
=-x(x²+2x)+x²+18x-17
=-x*16+x²+18x-17
=x²+2x-17
=16-17
=-1 =-1
采纳!采纳!
x+1=√17
平方
x²+2x+1=17
x²+2x=16
原式=x^3(x²+2x)-17x^3-x²+18x-17
=16x^3-17x^3-x²+18x-17
=-x^3-x²+18x-17
=-x^3-2x²+x²+18x-17
=-x(x²+2x)+x²+18x-17
=-x*16+x²+18x-17
=x²+2x-17
=16-17
=-1 =-1
采纳!采纳!
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
则(x+1)^2=17
化简得 x^2+2x = 16
x^5+2x^4-17x^3-x^2+18x-16
= x^3(x^2+2x) -17x^3-x^2+18x-17
= 16x^3 -17x^3-x^2+18x-17
= -x^3 - x^2 +18x-1
= -x(x^2+2x) +x^2 +18x-17
= -16x +x^2+18x-17
= x^2+2x -17
= 16 -17
= -1
化简得 x^2+2x = 16
x^5+2x^4-17x^3-x^2+18x-16
= x^3(x^2+2x) -17x^3-x^2+18x-17
= 16x^3 -17x^3-x^2+18x-17
= -x^3 - x^2 +18x-1
= -x(x^2+2x) +x^2 +18x-17
= -16x +x^2+18x-17
= x^2+2x -17
= 16 -17
= -1
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询